Synthesis of doped LiNi1/3Mn1/3Co1/3O2 (NMC 111) using combustion method and their electrochemical performance as cathode materials for li-ion batteries application / Kelimah Anak Elong - Anak Elong, Kelimah (2024)
The NMC 111 cathode materials possess compelling characteristics in terms of high energy density and low cost, making them highly promising for the next generation of high-energy lithium-ion batteries. However, they still encounter challenges, particularly rapid capacity degradation, especially under high C rates. In this study, we employed the combustion method to synthesize the NMC 111 cathode materials. The work was divided into three parts: (i) synthesis of the NMC 111 materials using three different fuels to investigate their phase, structure, morphology, and battery performance, (ii) synthesis of doped NMC 111 materials with two dopants (Titanium and Aluminium) to examine their impact on the structural, morphological, and battery performance, and (iii) optimization of the synthesis process to identify the best materials, NMCT, and evaluate their effects on the structure, morphology, and battery performance. In the first part, pristine NMC 111 materials synthesized using citric acid (NMCC) as a fuel demonstrated the most favorable performance, exhibiting the highest initial discharge capacity of 130.80 mAhg"1 and an efficiency of 89.84% after 30 cycles. Several factors contributed to this performance, including the highest enthalpy of combustion (AcH° solid), which influenced the crystal growth and ordered structure of the material, as well as a stable structure with reduced cation mixing and uniform distribution of partiele size, resulting in a larger surface area that facilitated the movement of Li ions during the charge-discharge process. In the second part, NMCT, which is NMC 111 doped with Titanium, exhibited superior performance compared to the Al-doped and pristine samples, delivering a higher initial discharge capacity of 142.51 mAhg"1 and an efficiency of 82.63% after 30 cycles. This enhanced performance can be attributed to factors such as increased crystallinity, a well-defined layered structure, improved cation ordering, and a smaller crystallite size. In the third part, the NMCT materials underwent annealing at various temperatures and durations. The NMCT annealed at 800 °C for 72 hours demonstrated excellent cycling stability, showcasing a higher initial discharge capacity of 148.6 mAhg"1 and capacity retention of 96.8% after 30 cycles. The exceptional performance of this material can be attributed to its superior structural integrity, characterized by larger parameters of the caxis, minimal cation mixing, larger Li-0 atomic distance, and a smaller potential difference (AE). In conclusion, the NMCT annealed at 800 °C for 72 hours emerged as the most favorable cathode material, exhibiting great potential for application in lithiumion batteries.